A magnetic solid phase extraction based on UiO-67@GO@Fe3O4 coupled with UPLC-MS/MS for the determination of nitroimidazoles and benzimidazoles in honey. (30th March 2022) - Xu, Yan; Li, Zuguang; Yang, Hua; Ji, Xiaofeng; Zhang, Hu; Li, Yinghong; Zhou, Min; Wang, Jianmei; Qian, Mingrong
Highlights: A novel metal–organic framework UiO-67@GO@Fe3 O4 was synthesized by a one-step. An efficient and environment-friendly MSPE-UPLC-MS/MS method was established. High sensitivity for nitroimidazoles/benzimidazoles detection in honey was acquired. Abstract: A novel composite material consisting of zirconium biphenyldicarboxylate metal–organic framework, graphite oxide and ferroferric oxide was fabricated by a facile one-step method and served as a magnetic solid phase extraction sorbent for the simultaneous determination of nitroimidazoles and benzimidazoles in honey. The amount of graphite oxide for the synthesis of composite material and analysis parameters were optimized. The optimum parameters were: dipotassium hydrogen phosphate buffer solution (pH 6) as diluent solvent, adsorption time 10 min, desorption time 5 min, methanol/acetonitrile (1:1, V/V) as desorption solvent. The targets were detected by ultra-high performance liquid chromatography tandem mass spectrometry. The recoveries of twelve analytes ranged in 70.5%-103.4% with relative standard deviations lower than 12.9% ( n = 3). The quantification limits were 0.2–0.6 μg/kg. Using the composite material as sorbent, a simple, rapid and environmental-friendly method based on magnetic solid phase extraction was successfully developed for determination of seven nitroimidazoles and five benzimidazoles in honey.